Metabolic and Fluid Biomarkers Support Microglia Activation in Amyotrophic Lateral Sclerosis - Matteo Zanovello; Francesca Serani; Alen Bebeti; Federica Paredi; Giulia Quadrio; Andrea Fortuna; Giacomo Maria Minicuci; Elena Pegoraro; Annachiara Cagnin; Diego Cecchin; Gianni Sorarù (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Amyotrophic lateral sclerosis is an incurable neurodegenerative disease involving motor neuron degeneration and metabolic and immune dysfunction. We combined clinical data, cerebrospinal fluid biomarkers and fluorodeoxyglucose positron emission tomography with magnetic resonance imaging to investigate the role of reactive microglia in disease pathogenesis. Patients showed increased cerebrospinal fluid levels of neurofilament light chain and chitinases, along with hypermetabolism in the medulla oblongata. Chitinase levels correlated with brainstem metabolism and clinical severity. These findings suggest a link between microglial activation, brainstem hypermetabolism and disease progression in amyotrophic lateral sclerosis, supporting a central role for neuroinflammation in disease pathogenesis.